2016
DOI: 10.1016/j.ebiom.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Therapeutics in Cancer — An Emerging Concept

Abstract: MicroRNAs (miRNAs) are an evolutionarily conserved class of small, regulatory non-coding RNAs that negatively regulate protein coding gene and other non-coding transcripts expression. miRNAs have been established as master regulators of cellular processes, and they play a vital role in tumor initiation, progression and metastasis. Further, widespread deregulation of microRNAs have been reported in several cancers, with several microRNAs playing oncogenic and tumor suppressive roles. Based on these, miRNAs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
325
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(346 citation statements)
references
References 94 publications
3
325
0
6
Order By: Relevance
“…Although the roles of HGF and VEGF have been discovered, the mechanisms underlying the up-regulation of HGF expression, especially in the tumorigenesis of GC, remain largely unknown. microRNAs (miRNAs) are a class of small noncoding RNAs (~22 bp) that are believed to regulate gene expression by directly binding with the 3'UTR of target mRNAs, causing translational inhibition or mRNA degradation [16]. Some miRNAs are closely related to the tumor formation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the roles of HGF and VEGF have been discovered, the mechanisms underlying the up-regulation of HGF expression, especially in the tumorigenesis of GC, remain largely unknown. microRNAs (miRNAs) are a class of small noncoding RNAs (~22 bp) that are believed to regulate gene expression by directly binding with the 3'UTR of target mRNAs, causing translational inhibition or mRNA degradation [16]. Some miRNAs are closely related to the tumor formation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, phase I and II clinical trials involving microRNA-based therapies, i.e. treatment of cancer patients with a liposome-formulated mimic of the tumor suppressor miR-34 (MRX34), have not yet yielded valuable drugs (18). However, it is conceivable that therapeutic approaches aimed at increasing plasma miR-499-5p levels will be developed in the future that can be of benefit for high risk cardiovascular disease patients.…”
mentioning
confidence: 99%
“…Several miRs have been reported to have an important role in tumor metastasis (45)(46)(47). Furthermore, since miRs regulate multiple target genes simultaneously, miR-based therapy is expected to be more efficient than the traditional single target therapy (48,49). In the present study, miR-429 was shown to be an important regulator in tumor cell migration and invasion, which emphasized an essential role of miR-429 in regulating GC metastasis.…”
Section: Discussionmentioning
confidence: 64%